Improving Infant Sleep Safety Through a Comprehensive Hospital-Based Program. (March 2015) - Goodstein, Michael H.; Bell, Theodore; Krugman, Scott D.
We evaluated a comprehensive hospital-based infant safe sleep education program on parental education and safe sleep behaviors in the home using a cross-sectional survey of new parents at hospital discharge (HD) and 4-month follow-up (F/U). Knowledge and practices of infant safe sleep were compared to the National Infant Sleep Position Study benchmark. There were 1092 HD and 490 F/U surveys. Supine sleep knowledge was 99.8% at HD; 94.8% of families planned to always use this position. At F/U, 97.3% retained supine knowledge, and 84.9% maintained this position exclusively ( P < .01). Knowledge of crib as safest surface was 99.8% at HD and 99.5% F/U. Use in the parents' room fell to 91.9% (HD) and 68.2% (F/U). Compared to the National Infant Sleep Position Study, the F/U group was more likely to use supine positioning and a bassinette or crib. Reinforcing the infant sleep safety message through intensive hospital-based education improves parental compliance with sudden infant death syndrome risk reduction guidelines.